2018
DOI: 10.1098/rsos.171374
|View full text |Cite
|
Sign up to set email alerts
|

Study of mixed mode fracture toughness and fracture trajectories in gypsum interlayers in corrosive environment

Abstract: Based on the engineering background of water dissolving mining for hydrocarbon storage in multi-laminated salt stratum, the mixed mode fracture toughness and fracture trajectory of gypsum interlayers soaked in half-saturated brine at various temperatures (20°C, 50°C and 80°C) were studied by using CSNBD (centrally straight-notched Brazilian disc) specimens with required inclination angles (0°, 7°, 15°, 22°, 30°, 45°, 60°, 75°, 90°) and SEM (scanning electron microscopy). The results showed: (i) The fracture lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
5
6
0
Order By: Relevance
“…The loading mode is characterized by the stress intensity factors K I and K II through the mixity parameter A key observation is that, in all cases shown in figure 13, the resulting fractures are tensile. Thus, mode I fracture is predicted by the model for all loading modes, with fracture patterns in agreement with both numerical and experimental observations reported in the literature [130][131][132][133]. Figures 14,15,and 16 show the fracture process for β 0 = 0 • , β 0 = 27 • , and β 0 = 90 • , respectively.…”
Section: Brazilian Splitting Testssupporting
confidence: 86%
See 2 more Smart Citations
“…The loading mode is characterized by the stress intensity factors K I and K II through the mixity parameter A key observation is that, in all cases shown in figure 13, the resulting fractures are tensile. Thus, mode I fracture is predicted by the model for all loading modes, with fracture patterns in agreement with both numerical and experimental observations reported in the literature [130][131][132][133]. Figures 14,15,and 16 show the fracture process for β 0 = 0 • , β 0 = 27 • , and β 0 = 90 • , respectively.…”
Section: Brazilian Splitting Testssupporting
confidence: 86%
“…As a consequence, the GMTS criterion takes into account the effect of both the T -stress and the fracture process zone. For pre-cracked Brazilian splitting tests, it has been shown experimentally [129,130,132] and numerically [133] that the MTS criterion strongly overestimates the initial crack propagation angle, while the GMTS criterion provides a much better agreement. Therefore, it is interesting to verify if the present model agrees with these observations.…”
Section: Brazilian Splitting Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when immersed for 30 h, the porosity in pure water at 80 • C were 2.59 times higher than that of half-saturated brine, and were 2.90 times higher than that of saturated brine. The comparison strongly confirmed that the chloride ion had an inhibitory effect on sodium sulphate dissolution, and the phenomenon could be explained by the Debye-Huckel theory, namely, sodium chloride was a symmetrical electrolyte [30][31][32][33]. When the concentration of sodium chloride solution was increased, the activity coefficient of calcium sulphate decreased and calcium sulphate formed ion pairs.…”
Section: The Effect Of Brine Concentration On Microstructure Of Glaubsupporting
confidence: 61%
“…According to the previous studies, it is widely recognized that fracture modes can be classified into 3 categories: transgranular fracture, intergranular fracture, and mixed fracture, which can be presented on the surface of the specimen. According to the research results of Zuo et al [1][2][3][4], it can be concluded that the roughness of the fracture surface after fracture is a comprehensive reflection of its microstructure, a magnitude of load and temperature [47,48]. erefore, the fracture trajectory is closely related to the roughness of the rock mass structural surface [49][50][51][52][53].…”
Section: Fracture Trajectorymentioning
confidence: 98%